(untitled) (قضايا سياسية, 2024)
There is no doubt that the emergence of new techniques, and the growth of interconnectedness and interdependence in the context of globalization, gives a particular severity and complexity to modern conflicts, where methods based on the integrated application of political, economic, media and other non-military measures are used. These techniques are called "hybrid" methods as they are implemented with the support of military force, and thus allow the political objectives of the conflict to be achieved with the least impact of military force on the enemy,There is no doubt that the emergence of new techniques, and the growth of interconnectedness and interdependence in the context of globalization, gives a particular severity and complexity to modern conflicts, where methods based on the integrated application of political, economic, media and other non-military measures are used. These techniques are called "hybrid" methods as they are implemented with the support of military force, and thus allow the political objectives of the conflict to be achieved with the least impact of military force on the enemy,hybrid wars and color revolutions. Strategies are consolidated through the interest of achieving political objectives with minimal impact of military force on the enemy through the use of modern information and knowledge techniques based on "soft power" and "hard power", Meanwhile, a combination of traditional and mixed types of modern conflicts is already a determining factor, a determining factor for all armed conflicts. So the use of hybrid methods in conflicts of a new type allows you to achieve the specified goal using the military intervention of non-state actors, traditional conflicts necessarily involve hybrid tehniques.